Learn You Some Erlang for Great Good: A Beginner's Guide - Hebert, Fred; Armstrong, Joe (No Starch Press, Incorporated, 2013)
Erlang is a functional programming language used by high paying companies such as Facebook and Amazon. Erlang is growing in popularity because it uniquely allows programmers to manage and modify running code live, thereby avoiding costly downtime. Erlang is also one of the few languages designed for concurrency, meaning it takes full advantage of all the processors in a single machine, or multiple machines connected in a cluster. In the spirit of Learn You a Haskell for Great Good! , Learn You Some Erlang for Great Good! is the highly anticipated book version of author Fred Hebert's extremely popular web tutorial. Heberts conversational, matter-of-fact tone, novel illustrations, and sometimes unusual sense of humor make the sometimes dense language palatable and fun to learn. This text is a refreshing change from the typical programming book.